2020
DOI: 10.1186/s13550-020-00699-x
|View full text |Cite
|
Sign up to set email alerts
|

TSPO PET detects acute neuroinflammation but not diffuse chronically activated MHCII microglia in the rat

Abstract: Background Accurate and sensitive imaging biomarkers are required to study the progression of white matter (WM) inflammation in neurodegenerative diseases. Radioligands targeting the translocator protein (TSPO) are considered sensitive indicators of neuroinflammation, but it is not clear how well the expression of TSPO coincides with major histocompatibility complex class II (MHCII) molecules in WM. This study aimed to test the ability of TSPO to detect activated WM microglia that are immunohistochemically pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…In agreement with these previous reports [118,119], Hu et al [120] reported no changes in [ 18 F]DPA-714 uptake in APP swe ×PS1 ΔE9 mice between 6 and 10 months of age with an increase in [ 18 F]DPA-714 SUVr becoming significant at 12 and 16 months of age. Now trying to understand the meaning of TSPO signal or lack of it, Al-Khishman et al [86] tried to determine the sensitivity of PET imaging to detect MHCII+ microglial cells as they did in a model of stroke (see above). Using the TgAPP21 transgenic rat model of AD and [ 18 F]FEPPA PET, they showed no significant increase in [ 18 F]FEPPA PET uptake in the TgAPP21 rats vs WT at 11-14 months of age, despite the same group demonstrating the presence of MHCII+ cells in previous reports [121,122].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with these previous reports [118,119], Hu et al [120] reported no changes in [ 18 F]DPA-714 uptake in APP swe ×PS1 ΔE9 mice between 6 and 10 months of age with an increase in [ 18 F]DPA-714 SUVr becoming significant at 12 and 16 months of age. Now trying to understand the meaning of TSPO signal or lack of it, Al-Khishman et al [86] tried to determine the sensitivity of PET imaging to detect MHCII+ microglial cells as they did in a model of stroke (see above). Using the TgAPP21 transgenic rat model of AD and [ 18 F]FEPPA PET, they showed no significant increase in [ 18 F]FEPPA PET uptake in the TgAPP21 rats vs WT at 11-14 months of age, despite the same group demonstrating the presence of MHCII+ cells in previous reports [121,122].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…and mean SUV 3 days post-MCAO • Significant decrease in max. and mean SUV by BMSC administration at 7 days post-MCAO • BMSC administration decreases infarct volume • [ 18 F]DPA-714 in vitro ARG confirmed in vivo PET data • BMSC administration decreases the number of CD8α+ T cells and CD68 microglia in the infarct and peri-infarct areas [ 101 ] [ 18 F]VUIIS1018A Evaluation of new TSPO tracer [ 18 F]VUIIS1018A 30-min intraluminal MCAO in male SD rats (7 weeks old, 220–240 g) 7–9 days post-MCAO • Ipsilateral [ 18 F]VUIIS1018A uptake at 0.73 SUV vs contralateral uptake at 0.20 SUV at 60 min post-injection • Ipsi-/contralateral ratio: 3.5 [ 18 F]VUIIS1018A in vitro ARG and TSPO IHC confirmed in vivo PET data [ 77 ] [ 11 C]DPA-713 [ 18 F]GE-180 Head-to-head comparisons of [ 11 C]DPA-713 and [ 18 F]GE-180 Permanent distal MCAO in 3-months-old female C57BL/6J mice 2, 6 and 28 days post-MCAO Ipsi-/contralateral ratio: • At 2 days, significant increase for [ 11 C]DPA-713 (1.22) but not for [ 18 F]GE-180 (1.10) • Significant increase for [ 11 C]DPA-713 and [ 18 F]GE-180 at 6 days (2.20 and 2.06, respectively) maintained at 28 days (1.67 and 1.64, respectively) • T2 MRI for ROI delineation • Ex vivo [ 11 C]DPA-713 and [ 18 F]GE-180 ARG confirmed the PET data • CD68 and GFAP IHC confirmed the presence of activated microglia and astrogliosis in the infarct [ 80 ] [ 18 F]FEPPA Test the ability of TSPO to detect MHCII + microglia in WM post-stroke Intrastriatal injection of ET1 in male Fischer 344 strain (11–14 months) Baseline and 7 and 28 days post-MCAO TSPO infarct/cerebellum ratio: • Baseline: 0.94±0.16 • Day 7: 2.10±0.78 • Day 28: 1.77±0.35 • Similar change in peri-infarct WM but not contralateral WM • T2 MRI for ROI delineation and co-registration • IHC for TSPO confirmed the presence of microglial activation in infarct and peri-infarct WM at day 7 • No increase in TSPO in peri-infarct WM at day 28 • Contralateral NI detected by OX6 MHC IHC at day 28 was not detected by PET imaging of TSPO/iNOS IHC [ 86 ] [ 18 F]DPA-714 ...…”
Section: Models Of Acute Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…With over a 20-year history, the field of molecular imaging is now wellentrenched [1][2][3] and continuing to expand its influence over multiple imaging modalities, including optical [4], nuclear [5], magnetic resonance (MR) [6] and acoustic [7]. In all these platforms, the use of contrast agents is a central theme, to enhance tissue structure and differentiate between healthy and diseased cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a transgenic rat model of AD, using second‐generation ligand [ 18 F]FEPPA, researchers were unable to detect activated microglia that were MHC‐II‐positive. Similarly, in a rat model of stroke, TSPO PET signal was only found in the insult region, but not in remotely present MHC‐II‐positive microglia [ 67 ].…”
Section: Introductionmentioning
confidence: 99%